Metatranscriptomic analysis revealed Prevotella as a potential biomarker of oropharyngeal microbiomes in SARS-CoV-2 infection - Lu, Sifen; Zhou, Yongzhao; Hu, Ya; Wang, Jing; Li, Honghao; Lin, Yifei; Wang, Denian; Xian, Jinghong; Zhao, Shengmei; Ma, Jinmin; Zhu, Zhongyi; Yang, Shengying; et al. (Frontiers in cellular and infection microbiology, 2023)
Disease severity and prognosis of coronavirus disease 2019 (COVID-19) disease with other viral infections can be affected by the oropharyngeal microbiome. However, limited research had been carried out to uncover how these diseases are differentially affected by the oropharyngeal microbiome of the patient. Here, we aimed to explore the characteristics of the oropharyngeal microbiota of COVID-19 patients and compare them with those of patients with similar symptoms. COVID-19 was diagnosed in patients through the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by quantitative reverse transcription polymerase chain reaction (RT-qPCR). Characterization of the oropharyngeal microbiome was performed by metatranscriptomic sequencing analyses of oropharyngeal swab specimens from 144 COVID-19 patients, 100 patients infected with other viruses, and 40 healthy volunteers. The oropharyngeal microbiome diversity in patients with SARS-CoV-2 infection was different from that of patients with other infections. and could play a role in the differentiation between patients with SARS-CoV-2 infection and patients with other infections. could also influence the prognosis of COVID-19 through a mechanism that potentially involved the sphingolipid metabolism regulation pathway. The oropharyngeal microbiome characterization was different between SARS-CoV-2 infection and infections caused by other viruses. could act as a biomarker for COVID-19 diagnosis and of host immune response evaluation in SARS-CoV-2 infection. In addition, the cross-talk among , SARS-CoV-2, and sphingolipid metabolism pathways could provide a basis for the precise diagnosis, prevention, control, and treatment of COVID-19.